Role Ambiguity, Goal Orientation and Turnover Intention among Faculty Members of Private Sector Universities - Gilani, Samreen; Anum Rabbani (Technium Social Sciences Journal, 2021)
The research was conducted to examine the relationship between, role ambiguity, goal orientation and turnover intention among faculty members of private sector universities and also to find out the moderating role of goal orientation in the relationship between role ambiguity and turnover intention. It was hypothesized that there would be a significant relationship among role ambiguity, goal orientation and turnover intention. It was also hypothesized that role ambiguity would predict turnover intention among teachers of private sector universities. Another hypothesis was that goal orientation would moderate the relationship between role ambiguity and turnover intention. And last hypothesis was that there would be significant relationship among demographic variables, role ambiguity, goal orientation and turnover intention. A sample of 250 faculty members (N = 250) age 30-45 (125 Male; 50%, 125 Females; 50%) of different private sector universities of Lahore was taken. The Role Ambiguity Scale (Rizzo et al., 1970), Goal Orientation Scale (Button, Mathieu & Zajac, 1996) and the Turnover Intention Scale (Roodt, 2004) were used to measure the study variables. Correlation analysis showed that there is positive relationship between role ambiguity and goal orientation. Role ambiguity and turnover intention have negative correlation. The results also showed that there is negative relationship between goal orientation and turnover intention. Findings also revealed role ambiguity to be the most significant predictor of turnover intention. Results also reported that there were non- significant gender difference in role ambiguity, goal orientation and turnover intention. The study can be implicated for many people including psychologists, teachers, researchers, business administrators, industrial workers and employees also helpful for them as well as their family.